FurA contributes to the oxidative stress response regulation of Mycobacterium avium ssp. paratuberculosis - Eckelt, Elke; Meißner, Thorsten; Meens, Jochen; Laarmann, Kristin; Nerlich, Andreas; Jarek, Michael; Weiss, Siegfried; Gerlach, Gerald-F.; Goethe, Ralph (Frontiers in Microbiology, 2015)
The ferric uptake regulator FurA is known to be involved in iron homeostasis and stress response in many bacteria. In mycobacteria the precise role of FurA is still unclear. In the presented study, we addressed the functional role of FurA in the ruminant pathogen Mycobacterium avium ssp. paratuberculosis (MAP) by construction of a furA deletion strain (MAP∆furA). RNA deep sequencing revealed that the FurA regulon consists of repressed and activated genes associated to stress response or intracellular survival. Not a single gene related to metal homeostasis was affected by furA deletion. A decisive role of FurA during intracellular survival in macrophages was shown by significantly enhanced survival of MAP∆furA compared to the wildtype, indicating that a principal task of mycobacterial FurA is oxidative stress response regulation in macrophages. This resistance was not associated with altered survival of mice after long term infection with MAP. Our results demonstrate for the first time, that mycobacterial FurA is not involved in the regulation of iron homeostasis. However, they provide strong evidence that FurA contributes to intracellular survival as an oxidative stress sensing regulator.